2004
DOI: 10.1073/pnas.0404911101
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide mediates Mn(II)-catalyzed decomposition of hydrogen peroxide and peroxidation reactions

Abstract: Mn(II) can catalyze the decomposition of H2O2 and, in the presence of H 2O2, can catalyze the oxidation of NADH. Strikingly, these processes depend on the simultaneous presence of both CO 2 and HCO 3 ؊ . This explains the exponential dependence of the rates on Materials and MethodsNaHCO 3 , MnCl 2 , sodium pyrophosphate, and H 2 O 2 were from Mallinckrodt; Tris was from Merck; catalase was from Roche Molecular Biochemicals; human MnSOD was from Biotechnology General (Rehovot, Israel); and NADH was from Sigma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 19 publications
0
57
1
Order By: Relevance
“…The t 1/2 for Ras turnover exceeds 12 hr 33 and since apoptosis approached 72% after only 4 hr of treatment, the data suggested that the effects of Man-A were probably not due to changes in Ras maturation. To examine this further, we used the method of Adjei et al, who demonstrated that prenylated proteins like Ras and HDJ2 migrate faster than their unprenylated counterparts on SDS-PAGE gels.…”
Section: Effects Of Manumycin-a On Ras Effector Status Ras and Protementioning
confidence: 87%
“…The t 1/2 for Ras turnover exceeds 12 hr 33 and since apoptosis approached 72% after only 4 hr of treatment, the data suggested that the effects of Man-A were probably not due to changes in Ras maturation. To examine this further, we used the method of Adjei et al, who demonstrated that prenylated proteins like Ras and HDJ2 migrate faster than their unprenylated counterparts on SDS-PAGE gels.…”
Section: Effects Of Manumycin-a On Ras Effector Status Ras and Protementioning
confidence: 87%
“…is not exclusive to Cu(II); instead, other metals, such as Fe(II), Mn(II), and Co(II), share a similar peroxynitrite-or H 2 O 2 -induced, (bi)carbonate-enhanced peroxidative activity without needing to be bound to proteins (6,18,19,23). The addition of (bi)carbonate to HSA incubated with H 2 O 2 and Cu(II) protected against protein fragmentation, but enhanced HSA-DMPO radical-derived nitrone adducts (Fig.…”
Section: Production Of Hsa Radicals By Copper-catalyzed Oxidation-resmentioning
confidence: 99%
“…In addition, (bi)carbonate buffer (BB) 1 (CO 2 , H 2 CO 3 , HCO 3 Ϫ and CO 3 Ϫ2 ) has not only become recognized as an important component in vivo and in cell culture maintenance of acid-base balance but has also been implicated in the modulation of the oxidative chemistry of peroxynitrite (16 -18) and other reactive oxygen species (19,20). Thus, (bi)carbonate could affect the mechanism of oxidative damage to proteins by copper-catalyzed oxidations.…”
mentioning
confidence: 99%
“…In these measurements the molecularity of the complexes were assumed based on simple chemical principles of charge balance. Mn-bicarbonate complexes have also been the subject of scrutiny by biologists owing to their efficiency in catalyzing the dismutation of hydrogen peroxide, also known as its 'pseudo-catalase' activity 16,17 . The observed pseudocatalase rates have been used as an indirect probe for the molecularity of these complexes.…”
Section: Introductionmentioning
confidence: 99%